Elevated plasma proprotein convertase subtilisin/kexin type-9 is associated with poor prognosis of acute myocardial infarction in hypertension patients - Xiao-Qin Wen; Kui Huang; Jie Li; Li-Xue Wu; Bo Gao (European Journal of Inflammation, 2022)
Whether serum proprotein convertase subtilisin/kexin type 9 (PCSK9) affects the prognosis of patients after the percutaneous coronary intervention (PCI) in hypertension patients remains unknown. A total of 2350 acute myocardial infarction (AMI) subjects with hypertension after PCI were enrolled. Subjects were under 30-months follow-up and divided into the major cardiovascular adverse event (MACE) Group and the non-MACE Group. Cox regression analysis were performed for the risk factors of occurrence of MACE. The relationship between the level of PCSK9 and Gensin score was analyzed by Pearson correlation. Two hundred and thirty-two patients were divided to the MACE Group. Age over 55 (hazard ratio (HR) = 2.52; p = 0.032), smoking (HR = 1.02; p < 0.001), diabetes mellitus (HR = 1.35; p < 0.001) and PCSK9 levels over 1011.3 ng/mL (HR = 1.05; ptdf < 0.001) were risk factors of occurrence of MACE. Baseline levels of PCSK9 was significantly related with Gensini score in ST segment elevation myocardial infarction (STEMI) patients ( r = 0.51), all patients ( r = 0.37) and non-STEMI patients ( r = 0.34, p < 0.001). A high baseline PCSK9 level was the risk factor of poor prognosis of AMI patients with hypertension after PCI. PCSK9 levels were associated with the Gensini score in STEMI patients. Trial registration: This trial was registered at clinicaltrials.gov as NCT04100434.